1995
DOI: 10.1016/0895-7061(95)00023-i
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antihypertensive treatment on the increased β-adrenoceptor density in patients with essential hypertension

Abstract: The effect of different antihypertensive drugs on the increased surface beta 2-adrenoceptor density in essential hypertension was evaluated to elucidate whether the possible effect of the treatment on these receptors was secondary to blood pressure decreases or a specific effect of the drugs. Thirty-nine untreated essential hypertensive patients and 28 normotensive control subjects were studied in basal conditions. Hypertensive patients were randomly assigned to three treatment groups: bisoprolol (10 mg/day, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The Arg16Gly genotype had 7.3 mmHg higher systolic blood pressure than the Arg16Arg genotype, independently of WHR. It has been implied that the β 2 ‐adrenergic receptor function may play a pathogenic role in essential hypertension, and an increased surface β 2 ‐adrenergic receptor density in lymphocytes has been reported in hypertensive subjects [23]. Moreover, the upregulation of the β 2 ‐adrenergic receptor density after intravenous administration of clonidine seems to be slower in hypertensives [24].…”
Section: Discussionmentioning
confidence: 99%
“…The Arg16Gly genotype had 7.3 mmHg higher systolic blood pressure than the Arg16Arg genotype, independently of WHR. It has been implied that the β 2 ‐adrenergic receptor function may play a pathogenic role in essential hypertension, and an increased surface β 2 ‐adrenergic receptor density in lymphocytes has been reported in hypertensive subjects [23]. Moreover, the upregulation of the β 2 ‐adrenergic receptor density after intravenous administration of clonidine seems to be slower in hypertensives [24].…”
Section: Discussionmentioning
confidence: 99%
“…The current study also examined the unique and joint effect of ethnicity, gender, and age on β 2 ‐adrenergic receptors on peripheral blood mononuclear cells. It has been suggested that individual differences in the β‐adrenergic receptor may account, in part, for the disparity in the prevalence of hypertension between Blacks and Whites (Bono et al, 1995; Brodde, Stuka, & Demuth, 1985; Brushi, Orlandini, & Pavarini, 1984; Calls et al, 2000; Feldman, Limbird, Nadeau, Roberston, & Wood, 1984). Although not entirely consistent, previous studies of healthy persons and those with diagnosed hypertension have reported independent effects of ethnicity, gender, and age with β 2 ‐adrenergic receptor number ( B max ), dissociation constant ( K d ), and cyclic adenosine monophosphate (AMP) production in response to agonist stimulation (Cases et al, 1991; Halper et al, 1984; Kafka et al, 1979; Mader & Davis, 1989; Michel, Brodde, & Insel, 1990; Mills, Dimsdale, Ziegler, & Nelesen, 1995; Muller, Weller, & Krone, 1994; Trimarco et al, 1983), as well as ethnic‐ (e.g., Sherwood & Hinderliter, 1993; Stein, Lang, Singh, He, & Wood, 2000; Watkins, Dimsdale, & Ziegler, 1995) and age‐related (Bertel, Buhler, Kiowski, & Lutold, 1980) differences in beta‐adrenergic responsiveness to agonist stimulation.…”
mentioning
confidence: 99%
“…37 In a subsequent study Iaccarino et al 41 investigated the effects of β 2 AR variants on the left ventricular mass index (LVMi) regression when BP is reduced with β 1 -blockers (Atenolol), which are unable to completely block β 2 AR, 69,70 rather than with angiotensin-converting enzyme (ACE) inhibitors (Enalapril), which in hypertension reduce the whole sympathetic discharge. [71][72][73] This study showed that Glu27 patients presented a higher reduction in LVMi than Gln27 patients independently from treatment. 41 Moreover, the patients harboring Glu27 β 2 AR showed a larger regression of LVMi when treated with enalapril rather than atenolol.…”
Section: β 2 Ar Gene Polymorphisms In Hypertensionmentioning
confidence: 56%